SCIENTIFIC POLICE: PERFORMANCE IN THE AREA OF CRIMINAL EXPERIENCE - Zeferino de Sousa, Marcelo (Revista Gênero e Interdisciplinaridade, 2024)
This article aims to provide guidance and carrer vision with na emphasis on the technical-scientific police. Based on historical search and academic training to work in technical police bodies.